A Road Not Taken: Substance Abuse Programming in the New York City Jail System. (January 2015) - Selling, Daniel; Lee, David; Solimo, Angela; Venters, Homer
Substance abuse represents one of the most common diagnoses in jail settings and features prominently in the path into criminal justice involvement. In addition, substance abuse plays a major role in mortality, morbidity, and recidivism after release from jail. In 2008, a substance abuse treatment program was begun within the New York City jail system, the nation's second largest. This program, A Road Not Taken (ARNT), works collaboratively with courts, security officials within the jail, and community programs to identify inmates who have substance abuse concerns and provide in-jail programming and coordination of treatment after jail. An evaluation of ARNT participants revealed that they experienced a lower rate in incarceration after their program participation than they did before participation.